Žemininkai Literary Movement in Vilnius: Relationship with the Space of a Multinational City - Kvietkauskas, Mindaugas (Literatūra, 2023)
The article examines the relationship between the generation of žemininkai (a literary movement; its name can be roughly translated as ‘representatives of land’) and the multi-ethnic Vilnius urban space since 1940, when the young representatives of this generation moved to the regained capital of Lithuania. Previous studies of their work stated that the experience of Vilnius had a significant impact on the cultural consciousness of this generation, but they never analysed the process of development of their ‘Vilnius identity’ and urban discourse, the meanings of the city that it emphasised, and the manifestations of the relationship with the multi-ethnic urban environment and the cultural ‘other’. The article presents socio-cultural analysis of the poetic and ego-documentary texts of four žemininkai authors who reflected on their Vilnius experience – Pranė Aukštikalnytė-Jokimaitienė, Kazys Bradūnas, Vytautas Mačernis, and Alfonsas Nyka-Niliūnas, as well as the autobiographical testimonies of the literary scholar Vanda Zaborskaitė. Their initial attitudes seem to be similar – ethnocentric and monological, whereas the urban imagination is dominated by the axis of the Lithuanian-European cultural meanings, and the spatial images are distilled from the signs of the local cultural ‘Other’. However, as early as during the war years, and especially in the post-war period, a shift in the individual attitudes of some of the žemininkai is evident. The initial nationalistic schemes are loosened or questioned, and signs of the ‘Other’ are integrated, which is first of all manifested in their poetry and poetic prose about Vilnius.
Keywords: žemininkai generation; Vilnius; urban space; cultural Other; Holocaust memory